PRIVATIZATION OF PUBLIC ENTERPRISE: A TOOL FOR NIGERIAN ECONOMIC DEVELOPMENT (Singaporean Journal of Business Economics and Management, 2015)
The need for privatization of public enterprises in Nigeria, as it had been in most countries that adopted the public sector reform technique, was geared towards making the enterprises more efficient, effective and productive, such organizations could be longer be maintained by the government because they had become a financial burden to the public budget. Thus, privatization became the panacea for alleviating the government problems of owning and managing public enterprises, and at the same time, ensuring that such enterprises, when transferred to private ownership, would significantly improve economic development of the nation. This study examined privatization of public enterprises as a tool for economic development. The foremost utility company in charge of electricity, distribution in Lagos State Eko Electricity Distribution Company was used as a case study. The study used both Primary and Secondary source of data. The population study of 220, using WALPO sampling size of 30% which is 66. The questionnaire was based on the sample size. 60 valid while 6 invalid after the retrieved of the questionnaire. Two hypotheses formulated were tested using SPSS (ANOVA). The findings, of the study revealed that there is significant improvement in the productivity of the privatized enterprises. However, it was discovered that privatization is necessary to make public enterprises financially disciplined. The study recommend among others that the policy makers review the ongoing privatization programmed that privatized enterprise can perform better than what we are experiencing.